CRISPR arrays as high-resolution markers to track microbial transmission during influenza infection - Lingdi Zhang; Jahan Rahman; Matthew Chung; Lauren Lashua; Aubree Gordon; Angel Balmaseda; Guillermina Kuan; Richard Bonneau; Elodie Ghedin (Microbiome, 2023)
Abstract Background Disruption of the microbial community in the respiratory tract due to infections, like influenza, could impact transmission of bacterial pathogens. Using samples from a household study, we determined whether metagenomic-type analyses of the microbiome provide the resolution necessary to track transmission of airway bacteria. Microbiome studies have shown that the microbial community across various body sites tends to be more similar between individuals who cohabit in the same household than between individuals from different households. We tested whether there was increased sharing of bacteria from the airways within households with influenza infections as compared to control households with no influenza. Results We obtained 221 respiratory samples that were collected from 54 individuals at 4 to 5 time points across 10 households, with and without influenza infection, in Managua, Nicaragua. From these samples, we generated metagenomic (whole genome shotgun sequencing) datasets to profile microbial taxonomy. Overall, specific bacteria and phages were differentially abundant between influenza positive households and control (no influenza infection) households, with bacteria like Rothia, and phages like Staphylococcus P68virus that were significantly enriched in the influenza-positive households. We identified CRISPR spacers detected in the metagenomic sequence reads and used these to track bacteria transmission within and across households. We observed a clear sharing of bacterial commensals and pathobionts, such as Rothia, Neisseria, and Prevotella, within and between households. However, due to the relatively small number of households in our study, we could not determine if there was a correlation between increased bacterial transmission and influenza infection. Conclusion We observed that airway microbial composition differences across households were associated with what appeared to be different susceptibility to influenza infection. We also demonstrate that CRISPR spacers from the whole microbial community can be used as markers to study bacterial transmission between individuals. Although additional evidence is needed to study transmission of specific bacterial strains, we observed sharing of respiratory commensals and pathobionts within and across households. Video Abstract